2013
DOI: 10.1371/journal.pntd.0002329
|View full text |Cite
|
Sign up to set email alerts
|

The Malnutrition-Related Increase in Early Visceralization of Leishmania donovani Is Associated with a Reduced Number of Lymph Node Phagocytes and Altered Conduit System Flow

Abstract: In a murine model of moderate childhood malnutrition we found that polynutrient deficiency led to a 4–5-fold increase in early visceralization of L. donovani (3 days post-infection) following cutaneous infection and a 16-fold decrease in lymph node barrier function (p<0.04 for all). To begin to understand the mechanistic basis for this malnutrition-related parasite dissemination we analyzed the cellularity, architecture, and function of the skin-draining lymph node. There was no difference in the localization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
53
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 60 publications
(81 reference statements)
0
53
1
Order By: Relevance
“…Ϫ/Ϫ mice, we found no change in the localization of uninfected or L. donovaniinfected myeloid cells within the lymph node (18). This contrasts with the reduced migration of Langerhans cells to the lymph nodes and retention of those cells in the subcapsular sinus in CCR2 Ϫ/Ϫ mice infected with L. major (39).…”
Section: Discussioncontrasting
confidence: 75%
See 4 more Smart Citations
“…Ϫ/Ϫ mice, we found no change in the localization of uninfected or L. donovaniinfected myeloid cells within the lymph node (18). This contrasts with the reduced migration of Langerhans cells to the lymph nodes and retention of those cells in the subcapsular sinus in CCR2 Ϫ/Ϫ mice infected with L. major (39).…”
Section: Discussioncontrasting
confidence: 75%
“…In our previous studies, we found increased early visceralization following inoculation of L. donovani in the skin of malnourished mice. The increased numbers of visceral parasites in the malnourished group was not the result of impaired parasite killing but was due to parasites escaping the barrier function of the skin-draining lymph node (15,18). We also demonstrated a reduced number of macrophages, neutrophils, and DCs in the lymph nodes of malnourished mice (18).…”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations